Effects of Dietary Inclusion of Oil Palm Seed Meal in The Diet on The Production Performance of Growing Native Chickens - syahro ali Akbar; Rica Mega Sari; Nurhaita Nurhaita; Yusuf Lenonard Henuk (Department of Agriculture, 2022)
An experiment was conducted for 12 weeks to determine the effects of dietary inclusion of oil palm seed meal in the diet on the production performance of growing native chickens. 60 unsexed native chicks used in this study. They were randomly allotted into receive four dietary treatments with five replicates of three chicks/replicate. Dietary treatments were formulated according to NRC (1994) recommendations, and the four dietary treatments consisted of T0, T1, T2, and T3 supplemented with 0%ˏ 25%ˏ 50% and 75% of dietary inclusion of oil palm seed meal in the commercial diet supplied by Sinta Prima Feed Mill Indonesiaˏ and they contained 3000, 2688, 2375 and 2063 kkal/kg of metabolisable energy and 21, 17, 13, and 9% crude protein respectively. The parameters measured were feed intake, feed conversion, body weight gain, body weight, carcass percentage and income over feed cost (IOFC). Dietary inclusion of oil palm seed meal in the diet for native chickens resulted highly significant (P <0.01) feed intake, feed conversion ratio, body weight gainˏ body weight and IOFC. While dietary inclusion of oil palm seed meal in their diets produced no significant effect (P> 0.05) on their percentage of carcasses. In conclusionˏ dietary oil palm seed meal can be included up to 50% in the diet of native chickens until the age of 12 weeks, and resulted in their weight gain were relatively similar to the control diet with their feed conversion ratio was the lowest compared with other treatments